Penyelesaian Sengketa Pegadaian Syariah Melalui Badan Penyelesaian Sengketa Konsumen (BPSK) - Eka Choirunisa; Abdul Mujib (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Dispute resolution institutions can be used both for litigation and non-litigation dispute resolution. One of the dispute resolution institutions is the Consumer Dispute Settlement Agency (BPSK), which is regulated in Law Number 8 of 1999 concerning Consumer Protection. The UUPK and BPSK procedural law spell out the responsibilities and authorities of the BPSK. Currently, there are no restrictions on the types of consumer disputes that can be handled by BPSK with business actors and consumers. Regarding the authority of the BPSK in solving problems, especially in the field of Islamic finance, it is often the subject of discussion considering that each institution has different juridical foundations. The research method used is qualitative research using a juridical-normative approach. In Dispute Resolution at BPSK, the parties must first reach an agreement in the form of a contract before proceeding with dispute resolution through BPSK, which is basically a voluntary choice between the parties. BPSK cannot be used to resolve disputes if one party disagrees. Although envisioned as a weapon for consumers seeking justice, implementation remains challenging. This is because legal arrangements do not conform to assumptions, in particular answering buyer inquiries online quickly, effectively and efficiently. Apart from that, the UUPK articles are inconsistent, only contradictions between articles and horizontal conflicts with other statutory products. Legal certainty in dispute resolution requires gradual improvement of three components in the Consumer Dispute Settlement Agency: legal structure, legal substance, and legal culture. Keywords: Sharia Pawnshop Disputes, Consumer Dispute Settlement Agency (BPSK), Consumer Protection Act